Reconstructing the temperature and origin of CO2 mineralisation in CarbFix calcite using clumped, carbon and oxygen isotopes - Holdsworth, C.M.; John, C.M.; Snæbjörnsdóttir, S.Ó.; Johnson, G.; Sigfússon, B.; Leslie, R.; Haszeldine, R.S.; Gilfillan, S.M.V. (Applied geochemistry, 2024)
In-situ CO2 mineralisation has been demonstrated as a rapid and secure mechanism of geological CO2 storage through a series of field demonstrations in Icelandic basalts by Carbfix. A key indicator of success in the first of these tests was the discovery of newly precipitated calcite on the monitoring well downhole pump that contained the 14C tracer added to the injected CO2. In this study we use clumped, carbon and oxygen isotope measurements to determine the temperature of CO2 mineralisation and source of parental fluids and CO2 for the calcite found on the pump. Clumped isotope values (Δ47) range from 0.526‰ to 0.540‰, which correspond to mineralisation temperatures of 45–51 °C. These are 10–16 °C warmer than pre-injection temperatures measured at the pump depth. We attribute the warmer temperatures to continuous water pumping from the monitoring well, drawing up waters from deeper in the storage reservoir to the pump depth. Calculated parent fluid oxygen isotope values (δ18O) match well and local meteoric water records. Calcite carbon isotope values (δ13C) conform to a CarbFix injection source, but are higher than expected given previously established mineralisation yields for CarbFix. This is likely a consequence of the crystal homogenisation process required for analysis, resulting in an averaging of calcite δ13C values. The results of this study validate previous CarbFix findings that subsurface fluid migration and CO2 mineralisation occurred within porous media of the storage reservoir. This is as an example of how isotopic analysis of carbonates and CO2 can contribute to the verification of geological CO2 storage. [Display omitted] •Calcite that formed on monitoring well pump during CarbFix project analysed.•Clumped isotope Δ47 values correspond to mineralisation temperatures of 45–51 °C.•These are 10–16 °C warmer than pre-injection temperatures from the pump depth.•This is due to continuous water pumping, drawing up warmer deeper fluids.•Parental waters and CO2 isotope values match historic records.